Efficient and Practical Procedure for the Esterification of the Free α-Carboxylic Acid of Amino Acid Residues with β-(Trimethylsilyl)ethoxymethyl Chloride and Triisopropylsilyl Chloride - Suppo, Jean-Simon; de Sant’Ana, Danilo Pereira; Dias, Luiz Carlos; de Figueiredo, Renata Marcia; Campagne, Jean-Marc (Synthesis, 2014)
An efficient and practical procedure for the free α-carboxylic acid esterification of amino acid residues with β-(trimethylsilyl)ethoxymethyl chloride and triisopropylsilyl chloride is described. The reaction takes place under mild conditions and the expected protected amino acids are obtained in good to excellent yields. Our method provides a useful alternative for the C-terminal carboxylic acid protection of amino acids and peptides. Moreover, the removal of such protection was also achieved under mild conditions, without affecting either the other protecting groups at the α-amino moiety and side chains or the optical integrity at the α-position of the amino acid residues. Examples of their use in peptide synthesis are also illustrated.
Keywords: amino acids; protecting groups; carboxylic acids; synthetic methodology; peptides; organic synthesis